Environmental aging of reinforced polymer composite radome: reliability and performance investigation - Haider, Imran; Gul, Iftikhar Hussain; Aziz, Shahid; Faraz, Muhammad Iftikhar; Khan, Muhammad Ali; Jaffery, Syed Husain Imran; Jung, Dong-Won (Frontiers in Materials, 2024)
In high-speed microelectronics communication the efficient and reliable radome-enclosed antenna performance is highly desired which depends on consistent dielectric, mechanical properties, and low moisture absorption. The purpose this study is to investigate the dielectric properties of fiber-polymer matrix composite (PMC) radome over wideband frequency and impact of environmental aging on its performance. The objective is to evaluate the progressive degradation of radome properties/performance upon environmental aging High-silica fibers reinforced/epoxy (SF/Ex) composite radome and test specimens (40 to 90 (wt.%)) were fabricated. The dielectric constant (Ɛr) of SF/E0.8 (80 % fiber loading) composite radome material was decreased to 4% from its original value (3.93) and dielectric loss (δ) was reduced by 11% from 0.035 (2-18 GHz) while SEM morphology indicated fair interface bonding. Employing Hallberg and Peck model, equivalent aging time (5 to 25 years), upon accelerated environmental aging, the Ɛr was raised up to 3.69% , δ to 9.68%, moisture uptake in SF/E0.8 composite was increased from 1.13 % to 1.67 %, while tensile strength was retained up to 90.62% of its original value (147.83 MPa), compression strength up to 93.56% of (388.54 MPa), flexural strength up to 85.44 % of (286.77 MPa), and interlaminar shear strength up to 77.66% of (22.03 MPa) respectively. SF/E0.8 radome-enclosed antenna Gain was decreased to 1% and voltage standing wave ratio (VSWR) was raised to 1.04% and from their original values. This gradual and small deviation of SF/Ex composite properties and radome electrical performance, over the extended aging time, is referred to as reliable and effective for radome applications.